Comparative Analysis of Clinical and Environmental Strains of Exophiala spinifera by Long-Reads Sequencing and RNAseq Reveal Adaptive Strategies - Song, Yinggai; Du, Minghao; Menezes da Silva, Nickolas; Yang, Ence; Vicente, Vania A.; Sybren de Hoog, G.; Li, Ruoyu (Frontiers in Microbiology, 2020)
Exophiala spinifera, a capsule-producing black yeast, is overrepresented as agent of disseminated infection in humans with inherited dysfunction of the CARD9 gene. In a review of published CARD9 deficiency cases, black fungi were linked to mutations other than those prevalent in yeast and dermatophyte cases, and were found to respond to a larger panel of cytokines. Here, we sequenced and annotated the genomes of BMU 08022 from a patient with CARD9 deficiency and two environmental strains, BMU 00051 and BMU 00047. We performed genomic and transcriptomic analysis for these isolates including published black yeasts genomes, using a combination of long-read (PACBIO) and short-read (Illumina) sequencing technologies with a hybrid assembly strategy. We identified the virulence factors, fitness, and the major genetic and gene expression differences between the strains with RNAseq technology. Genome assembly reached sub-chromosome level with between 12,043 and 12,130 predicted genes. The number of indels identified in the clinical strain was higher than observed in environmental strains. We identify a relatively large core genome of 9,887 genes. Moreover, substantial syntenic rearrangements of scaffolds I and III in the CARD9-related isolate were detected. Seventeen gene clusters were involved in the production of secondary metabolites. PKS-cluster 17 was consistently found to be absent in the clinical strain. Comparative transcriptome analysis demonstrated that 16 single-copy genes were significantly differentially expressed upon incubation in brain-heart infusion broth vs. Sabouraud glucose broth. Most of the single-copy genes upregulated with BHI were transporters. There were 48 unique genes differentially expressed exclusively to the clinical strain in two different media, including genes from various metabolic processes and transcriptional regulation. Up-regulated genes in the clinical strain with Gene Ontology (GO) enrichment are mainly involved in transmembrane transport, biosynthetic process and metabolic process. This study has provided novel insights into understanding of strain-differences in intrinsic virulence of the species and indicated that intraspecific variability may be related to habitat choice. This indicates that strains of E. spinifera are differentially prone to cause infection in susceptible patient populations, and provides clues for future studies exploring the mechanisms of pathogenic and adaptive strategies of black yeasts in immunodeficient patients.